Protection of Forests of India from Animals - Krishnaswamy, V. S. (Indian Forester, 1953)
Some animals cause mechanical damage, some by browsing, some by stripping the barks of trees, some by destroying seeds, seedlings and roots, while some cause damage by grazing. Elephants, rhinoceros, bison and' pigs cause mechanical damage to the forests. The first two by damaging the fences erected in forests, facilitate the entrance of other animals into the protected area. Bison also does a similar damage, but pigs cause considerable harm by uprooting seedlings, coppice shoots and seedlings. Trenches have been dug in the forest for affording protection against elephants and pigs. In some places stone walls have also been erected for protection against the latter. Fences and crude country bombs have also been tried against the pigs. Elephants, bisons, sambur and black bears are guilty of stripping the barks of trees. Elephants have a partiality for the bark of the Artocarpus integrifolia, while bison strip the bark of Acrocarpus fraxinifolius. Sambur peels off the bark of Chukrasia in addition. Black bears, strip the bark of many deodar, spruce and kail poles to lick the rising sap and the cambium layer. Elephants, bison, sambur, nilgai and members of the deer family, goats and sheep are guilty of browsing many forest species. While there is no direct remedy against damage by elephants and bisons, the other soft skinned game are kept out by game proof fencing. Live hedges are also tried. As camels, goats and sheep are domestic animals the remedy is to prohibit them from entering the forest. Hares and rats cause considerable destruction of seeds and seedlings and roots. Their damage can be minimized either by using poisoned baits or by cyanogassing them or by using wire nets. Grazing probably does more injury to the forest than even fire. The damage done by semi-wild cattle is kept down by capturing and selling them. In some places kheddah operations are also conducted to capture them. To minimize the damage done to the forest by the ordinary grazing cattle is rather difficult as it is closely bound with socio-political considerations. So long as regulation of grazing cannot be enforced, damage from excessive grazing by the domestic cattle cannot be minimized. The damage caused to the forests of India by animals are varied. Some animals cause mechanical damage, some by browsing some by stripping the barks of trees; some by destroying seeds, seedlings and roots; while some cause damage by grazing. The nature and extent of damage caused by these animals and the measure taken to counter these, are described in this paper.